Psychological Distress and Work Demands: A Systematic Review of Overload, Cognitive Appraisal, and Self-Regulation as Mediators with Meaning in Life as Moderator - Susan Rahmayani; Lydia Indira; Esiyannera Esiyannera; Fanny Yulianingsih (International Journal of Psychology and Health Science, 2026)
Psychological distress is an individual's negative response to prolonged workplace stressors, characterized by anxiety, depression, and emotional exhaustion. This study aims to analyze the effect of work demand on psychological distress through mediation of overload, cognitive appraisal, and self-regulation, with meaning in life moderating each mediator-to-outcome pathway. A Systematic Literature Review (SLR) was conducted on 40 reputable scientific articles from Scopus, Web of Science, ScienceDirect, and nationally SINTA-accredited journals, analyzed through thematic synthesis. Results indicate: (1) work demand significantly influences overload (H1); (2) work demand influences cognitive appraisal (H2); (3) work demand influences self-regulation (H3); (4) work demand directly influences psychological distress (H4); (5) overload (H5), cognitive appraisal (H6), and self-regulation (H7) each influence psychological distress; (6) work demand influences psychological distress through overload (H11), cognitive appraisal (H12), and self-regulation (H13); and (7) meaning in life moderates the effect of work demand on psychological distress through overload (H8), cognitive appraisal (H9), and self-regulation (H10). The proposed moderated mediation model provides a comprehensive framework for understanding psychological mechanisms of work demand on distress and offers directions for strengths-based workplace interventions.